(untitled) (Revista Nacional de Odontología, 2020)
Introduction: The increasing orthodontic service demands high-quality outcomes so the patient could be satisfied with the results, but scarce studies are addressing this topic. Objective: To assess the relationship between the quality of orthodontic treatment outcomes and patient satisfaction at an Orthodontic Clinic in a Colombian university. Methods: An observational cross-sectional study was conducted with a sample of 67 patients who completed their orthodontic treatment between February 2018 and June 2019. Satisfaction was assessed by a questionnaire consisting of 17 items. The quality of the orthodontic treatments was established with post-treatment study models and panoramic radiographs that were analyzed according to the eight criteria of the Objective Grading System (OGS) generated by the American Board of Orthodontics. Frequencies and proportions for qualitative variables and measures of central tendency and dispersion for quantitative ones were calculated. Chi-square test, Fisher exact test, and Pearson correlation coefficients were used as appropriate. P <0.05 was considered statistically significant. Results: Among the 67 participants, 49 (73.1%) were female, the average age was 21.4 ± 9.1 years, the average treatment duration was 32.3 ± 5.0 months, and the average defects was 28.8 ± 9.2. For the overall satisfaction score, 38.8% were very satisfied. There was not a relationship between patient satisfaction and the quality of the orthodontics treatments grouped in excellent, acceptable, and deficient according to the OGS criteria. Conclusions: No relationship was found between the quality of the orthodontic treatment outcomes measured by OGS criteria and patient satisfaction. These results showed that it is necessary to propose continuous improvement plans at the university center.